2012
DOI: 10.1007/s00383-012-3066-x
|View full text |Cite
|
Sign up to set email alerts
|

Role of lymphoscintigraphy and sentinel lymph node biopsy in the management of pediatric melanoma and sarcoma

Abstract: Purpose The purpose of this study was to describe the use of lymphoscintigraphy and sentinel lymph node biopsy for the management of children with melanoma and sarcomas. We report the experience of two children’s hospitals that utilize this technique to identify sentinel lymph nodes for lymph node biopsy and dissection. Methods We identified 56 patients (median age 10.8 years) who underwent 58 lymphoscintigraphy procedures. There were 33 patients with melanoma and melanocytic lesions, and 23 with sarcomas. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 28 publications
5
25
0
Order By: Relevance
“…reported that they achieved a feasibly high success rate (95%) to identify SN in patients with melanoma or sarcoma using combination of preoperative lymphoscintigraphy and intraoperative mapping (blue dye/gamma probe), which we performed in our current study. They also found the SN metastasis in one RMS patient out of six cases (16.7%) who underwent lymphoscintigraphy/SLNB whereas no SN metastasis was observed in patients with non‐RMS sarcomas (0/17) . Those findings were consistent with results from previous reports with 11.1–33.3% SN positivity rate for RMS patients …”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…reported that they achieved a feasibly high success rate (95%) to identify SN in patients with melanoma or sarcoma using combination of preoperative lymphoscintigraphy and intraoperative mapping (blue dye/gamma probe), which we performed in our current study. They also found the SN metastasis in one RMS patient out of six cases (16.7%) who underwent lymphoscintigraphy/SLNB whereas no SN metastasis was observed in patients with non‐RMS sarcomas (0/17) . Those findings were consistent with results from previous reports with 11.1–33.3% SN positivity rate for RMS patients …”
Section: Discussionsupporting
confidence: 89%
“…Several papers have been published to demonstrate SLNB on a variety of childhood malignancies, such as melanomas, RMS, non‐RMS soft tissue sarcomas and breast cancers . Parida et al . reported that they achieved a feasibly high success rate (95%) to identify SN in patients with melanoma or sarcoma using combination of preoperative lymphoscintigraphy and intraoperative mapping (blue dye/gamma probe), which we performed in our current study.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Sentinel lymph node biopsy (SLNB) was designed as a rational alternative to random sampling with the hypothesis that the first (sentinel) node to receive lymphatic drainage from a tumor site would be most likely to contain metastatic tumor. SLNB is widely used for cancers such as melanoma and breast cancer, and it has been used safely in pediatric melanoma and sarcoma . SLNB is performed via the injection of a technetium‐99m–labeled colloid tracer and lymphazurin blue dye at the tumor site.…”
Section: Introductionmentioning
confidence: 99%